Identifying terrorist attack victims - Elvire Arrighi; Amandine Matricon Charlot (Oxford University Press, 2020)
The terrorist attacks that occurred in France in 2015 and 2016, which had many victims, proved that it is essential to identify victims following the methodology developed by International Criminal Police Organization (INTERPOL) for such events. Initially designed for natural disasters, this approach must be strictly respected should a terrorist attack occur. This includes the specific collection of bodies and body parts, as well as the setup of an antemortem unit, postmortem unit, and Identification Commission. This commission is made up of specialists and will make decisions on the basis of primary identifying elements (fingerprints, DNA, dental records) and/or secondary identifying elements (other distinctive and particularly discriminating signs). A multidisciplinary team, combining specifically trained police officers and scientists, must provide a reliable and consolidated list of deceased people based on biometric elements cross checked with elements from the investigations. Any list of names generated on another basis should be excluded. Identification of the deceased by relatives (visual recognition), even if the bodies do not appear mutilated and/or decayed, should be avoided to avert erroneous death announcements, body presentations, or even burials or cremations. Similarly, identifying victims only on the basis of their personal effects (such as an identity card) must be absolutely avoided. All bodies, even those whose identities seem obvious to the first responders or to the relatives, must be registered as "X" during the crime scene search and properly identified according to the INTERPOL protocol. The same protocol should be applied to unconscious injured people. Considering the expectations of our modern society for rapid information circulation and quick responses from the authorities, the French team has made a few adjustments to speed up the identification process without compromising its integrity. Validated and supported by both the French judicial and administrative authorities in the light of the experience of the November 2015 attacks in Paris, this innovative method proved its effectiveness during the Nice attack in July 2016. It can only be successful in a context where all the individuals involved in the crisis, up to the highest authorities, understand it, support it, and relay it in the best interest of the victims' families.KEY POINTS The INTERPOL protocol must be used in order to identify victims after a terrorist attack. Some adaptations to the abovementioned protocol can be put in place in order to speed up the identification process in such circumstances. The lessons learned from the 2015 Paris terrorist attack can be useful to other disaster victim identification (DVI) units.